Carta del General Darling - Todd, Roberto H.; General Darling (My University, 1920)
Carta relacionada al status de Puerto Rico.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Puerto Rico. Legislature. House of Representatives.